The importance of psychologists within nursing homes : attitude of nursing home staff towards psychological services - Katla Marín Stefánsdóttir 1996- (2019)
Life expectancy has increased over the years, as a result people are living longer and are healthier than before. It is estimated that 23% of the nation’s population will be older adults by 2060 (Velferðarráðuneytið, 2014). The old-old adults (80 years and older) is the fastest growing population group. The rapid growth in the ageing population will result in increasing number of people requiring long-term care, such as in nursing homes (Cooney, 2012). Depression, along with other impairments, appears to be common among older adults, especially in nursing homes, where the prevalence is around 40%. Therefore, there is a need for psychological interventions in nursing homes. Unfortunately, psychological services are often not available in nursing homes in Iceland. No study has examined the attitude of nursing home staff towards psychological services for residents, staff members, and residents’ relatives. Thus, the aim of the current study is to examine the attitude of nursing home staff towards psychological services in nursing homes in Reykjavík, Iceland. A total of 145 nursing home staff members from 12 nursing homes in the capital area participated in the study. The majority of the participants were women (93.1%) and most (64.1%) had worked under five years in a nursing home. The largest age group was 18 – 24 year old’s (28.3%), followed by 55 – 59 years old (14.4%). The majority of the participants worked as caregivers (38.6%) or in Health and Welfare (34.5%). Result showed that participants considered psychological services to be useful for nursing home staff and residents and their relatives, F(2, 430) = 3.682, p=0,026. They also believed that psychological services could reduce drug use among residents. Furthermore, those who found psychological services to be necessary and important also believed drug use can be decreased F(2, 143) = 23.231, p<0.05. Neither education nor age predicted attitude towards psychological services, but period of employment slightly predicts attitude towards psychological ...